2010
DOI: 10.1063/1.3504615
|View full text |Cite
|
Sign up to set email alerts
|

Nonconventional magnetism in pristine and alkali doped In2O3: Density functional study

Abstract: Using In2O3 as a host matrix, extensive calculations based on density functional theory have been carried out to understand the electronic and magnetic properties of native defects, alkali and alkaline-earth metal substitutions as disputed in recent theoretical and experimental studies. Our calculations show that the magnetism in undoped In2O3 is originated from In vacancies (VIn) instead of O vacancies. The ferromagnetic (FM) coupling between the moments introduced by VIn is found strong enough to achieve roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…2 reveals that most of the spin density is localized in the vicinity of the dopant and its nearest neighboring N atoms, with a small contribution from the farther N atoms. Similar moment distributions have been found in Mg and Ca doped AlN [49,50], Mg, K, Al and Sr doped SnO 2 [43,44], Li doped TiO 2 [46] and alkali doped In 2 O 3 [45]. To study the magnetic coupling between the moments induced by doping, the systems Al 34 X 2 N 36 (X¼ Li, Na and K), in which two Al atoms are substituted by doping atoms X in the supercell, are investigated.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…2 reveals that most of the spin density is localized in the vicinity of the dopant and its nearest neighboring N atoms, with a small contribution from the farther N atoms. Similar moment distributions have been found in Mg and Ca doped AlN [49,50], Mg, K, Al and Sr doped SnO 2 [43,44], Li doped TiO 2 [46] and alkali doped In 2 O 3 [45]. To study the magnetic coupling between the moments induced by doping, the systems Al 34 X 2 N 36 (X¼ Li, Na and K), in which two Al atoms are substituted by doping atoms X in the supercell, are investigated.…”
Section: Resultsmentioning
confidence: 55%
“…3-5, the 2p states of the N atoms overlap significantly near the Fermi level, suggesting a strong p-p hybridization interaction between them [29]. It has been reported that the introduced holes in 2p orbitals of the N atoms can couple with each other through this strong interaction [29,45]. Indeed, the calculated spin density in Fig.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…7 Recently, several experimental and theoretical reports showed that cation vacancies can induce magnetism not only in SnO 2 , but also in ZnO, TiO 2 , ZrO 2 , In 2 O 3 , CeO 2 , and HfO 2 . [8][9][10][11][12][13] Following the prediction of magnetism without TM impurities, much interest was also diverted to magnetism induced by light element doping in host semiconductor matrices, e.g., K, N, Mg, and C-doped SnO 2 . [14][15][16][17][18] There are experimental evidences which clearly demonstrate room temperature FM induced by light elements.…”
Section: Introductionmentioning
confidence: 99%